The mass media and family planing in Kenya - Westoff, Charles F.; Rodríguez, Germán (DHS Working Papers No. 4, 1993)
There is, understandably, a strong interest within population policy and family planning program circles in the potential impact on contraceptive behavior and reproductive preferences of mass media messages that try to inform and motivate people on the methods and advantages of regulating fertility.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
The Demographic and Health Surveys Program is designed to collect data on fertility, family planning, and maternal and child health. DHS is funded by the United States Agency for International Development. DHS Working Papers are intended to disseminate early findings of in-depth analysis of DHS data. Comments about this working paper or requests for information should be sent to: DHS, Macro International Inc., 8850 Stanford Boulevard, Suite 4000, Columbia, MD 21045, USA (Telephone 410-290-2800; Fax 410-290-2999).